Perspektif Al-Qur’an tentang Pemicu Kekerasan - Nyayu Khodijah (Ulumuna, 2011)
Analysis of Al-Qur’an on all facts on violence is related to the Qur’anic concept on human being, the concept of “Fitrah” and “behaviour”. Based on the interpretation of the Qur'an, the violence is not stated as a basic human nature as expressed by psychoanalysis, because all humans are born with the condition of “fitrah”. But during its developments, the fitrah is much influenced by the environment so that people do the violence. The factors are as follows: family, film, television including angriness—all make people aggressive and tend to do the violence—are claimed by Islam as something unaccepted. To avoid the harsh, people are asked to control their character and to do their religious obligation; such as praying and fasting.